2020
DOI: 10.1186/s13317-019-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Receptor autoimmunity: diagnostic and therapeutic implications

Abstract: Receptor autoimmunity is one of the ways in which autoimmune diseases appear in humans. Graves' disease, myasthenia gravis, idiopathic membranous nephropathy, and autoimmune acute encephalitis are the major autoimmune diseases belonging to this particular group. Receptor autoimmune disease are dependent on the presence of autoantibodies directed against cell-surface antigens, namely TSH receptor in thyrocytes, acetylcholine receptor in neuromuscular junction, phospholipase 2 receptor in podocytes, and NMDA rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
(79 reference statements)
1
7
0
Order By: Relevance
“…Risk alleles for THSD7A-associated MNs remain unclear. Collectively, the involvement of HLA-DQA1 and HLA-DRB1 in PLA2R-associated MN pathogenesis is consistent with the current knowledge for the importance of T-cell dependent and B-cell-mediated autoimmunity to anti-receptor-caused autoimmune diseases [ 73 ], which include the receptor PLA2R in PMN.…”
Section: Mechanisms Underlying Pla2r- and Thsd7a-contributed Mn Pathosupporting
confidence: 86%
“…Risk alleles for THSD7A-associated MNs remain unclear. Collectively, the involvement of HLA-DQA1 and HLA-DRB1 in PLA2R-associated MN pathogenesis is consistent with the current knowledge for the importance of T-cell dependent and B-cell-mediated autoimmunity to anti-receptor-caused autoimmune diseases [ 73 ], which include the receptor PLA2R in PMN.…”
Section: Mechanisms Underlying Pla2r- and Thsd7a-contributed Mn Pathosupporting
confidence: 86%
“…A reason for the low prevalence of GnRH-R-aAb may be given in the nature of the protein as a GPCR, with only small portions of the protein exposed to the extracellular space, i.e., the N-terminus and the three small extracellular loops. This feature may have also contributed to the relatively low concentrations of the GnRH-R-aAb identified, barely surpassing the noise level in several of the statistically positive samples, leaving three samples only with GnRH-R-aAb concentrations in a considerable range that may be disease-relevant, as the disruptive effects of aAb on physiological or endocrine pathways usually correlates to aAb titer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DEGs dataset of these leukocytes is displayed in Figure 2C and Dataset 3, except for monocytes, which were unable to be analyzed due to insufficient cell numbers. Also, the deficiency of meaningful differential genes in plasma cells, T cells, and mast cells was probably owing to the technical limits of isolating insufficient corresponding cells, since previous studies have confirmed their contributions in IMN (31)(32)(33). Macrophages highly expressed genes responsible for the regulation of leukocyte activation (ZFP36L2, AXL, and RPS3), inflammatory response (KNG1, ELF3, CXCR4, and LY86), and the antigen processing and presentation as well as immune response-regulating signaling pathway (HLA-DPA1, HLA-DPB1, and HLA-DRB1) (Figures 2D, E).…”
Section: Identification Of Degs and Enrichment Analysis In The Kidneymentioning
confidence: 99%